Navigating Between Right, Wrong, and Relevant: The Use of Mathematical Modeling in Preclinical Decision Making - Kondic, Anna; Bottino, Dean; Harrold, John; Kearns, Jeffrey D.; Musante, CJ; Odinecs, Aleksandrs; Ramanujan, Saroja; Selimkhanov, Jangir; Schoeberl, Birgit (Frontiers in Pharmacology, 2022)
The goal of this mini-review is to summarize the collective experience of the authors for how modeling and simulation approaches have been used to inform various decision points from discovery to First-In-Human clinical trials. The article is divided into a high-level overview of the types of problems that are being aided by modeling and simulation approaches. Detailed case studies around drug design (Nektar Therapeutics, Genentech), feasibility analysis (Novartis Pharmaceuticals), improvement of preclinical drug design (Pfizer), translational modeling to improve clinical drug design (Merck, Takeda and Amgen).